Using the activated sludge model 2d (ASM2d) to understand and predict the phosphorus accumulating organisms mechanism in enhanced biological phosphorus removal in relation to disintegrated sludge as a carbon source - Boontian, Nittaya (Cranfield University, 2012)
Carbon sources are considered as one of the most important factors in the performance of enhanced biological phosphorus removal (EBPR). Disintegrated sludge (DS) can act as carbon source to increase the efficiency of EBPR. This research explores the influence of DS upon phosphorus removal efficiency using mathematical simulation modeling. Activated Sludge Model No. 2d (ASM2d) is one of the most useful of activated sludge (AS) models. This is because ASM2d can express the integrated mechanisms of phosphorus accumulating organisms (PAOs) under aerobic, anaerobic and anoxic conditions. Cont/d.